Application and Comparison of Civil 3D and Revit in Hydraulic Building Modeling - SHU Yuren; QIU Zhenfeng; WANG Junjie (Renmin Zhujiang)
Both Civil 3D and Revit are building information modeling (BIM) software,and they can obtain different results when adopted to model hydraulic buildings.Civil 3D and Revit were used to model the dam hub project of Miaotang Reservoir Project in Wushan County,Chongqing,and the advantages and disadvantages of the two modeling methods were compared and analyzed in terms of their efficiency,accuracy,and quantity statistics in modeling upstream and downstream rockfill areas,core walls,spillways,and geology.The results show that Civil 3D has higher modeling efficiency and model accuracy when applied to the hydraulic dam and can be easily operated compared with Revit.It can provide a reference for similar engineering BIM methods.